Evaluation of the Efficacy of Romiplostim in Management of Chemotherapy-Induced Thrombocytopenia in Indian Patients: A Retrospective Study - Talreja, Vikas; Khatwani, Sangeeta; Subhagan, Priyanka (South Asian Journal of Cancer, 2025)
Chemotherapy-induced thrombocytopenia (CIT) is a frequent complication of antineoplastic therapy. The incidence of CIT varies with cancer type and regimen used. CIT can result in chemotherapy delays, dose reductions, and discontinuation, leading to reduced survival rates· Romiplostim is a thrombopoietin receptor agonist that is effective for the treatment of CIT.This article evaluates the efficacy and safety of romiplostim in patients with CIT in a real-world settingThe study was a retrospective, single-center study, which enrolled patients with solid tumors or hematological malignancies with persistent thrombocytopenia who had been treated with romiplostim.A total of 100 patients with CIT were categorized into three treatment groups: romiplostim 500 mcg (N = 56), romiplostim 500 mcg + 1-unit random donor platelets (RDP) (N = 35), and romiplostim 500 mcg + 2-unit RDP (N = 9). The most common malignancies were gallbladder carcinoma in the romiplostim 500 mcg group, breast cancer in the romiplostim 500 mcg + 1-unit RDP group (31.4%), and gallbladder and head and neck carcinoma in the romiplostim 500 mcg + 2-unit RDP group. Chemotherapy regimens varied, with gemcitabine + cisplatin (26.7%), Adriamycin + cyclophosphamide (31%), and paclitaxel + carboplatin (22%) being the most used in each group, respectively. Grade I thrombocytopenia was most frequent with Capox (22.2%), grade II with gemcitabine + cisplatin (42.3%), grade III with paclitaxel + carboplatin and gemcitabine + cisplatin (17.02%), and grade IV with paclitaxel + carboplatin (44.4%). Romiplostim significantly increased platelet counts across all groups (p < 0.001), demonstrating its effectiveness in managing CIT across all severity grades.Romiplostim was effective in increasing platelet counts regardless of the grade of thrombocytopenia. Romiplostim use for the management of CIT will help in correcting CIT and allow resumption of chemotherapy without recurrence of CIT in most patients undergoing cancer chemotherapy.
Keywords: cancer; chemotherapy-induced thrombocytopenia; malignancies; romiplostim; tumor